Strategi Manajemen Public Relations Starbucks dalam Pemulihan Reputasi Merek Pasca Krisis Global 2024–2026 - Nisa Mukti Rahayu; Lidya Imas Ayu; Marjam Desma Rahadhini (Jurnal of Management and Social Sciences, 2026)
The dynamics of the global coffee industry during the 2024–2026 period were characterized by significant fluctuations that placed Starbucks in a vulnerable position due to multidimensional reputation crises, ranging from geopolitical sentiments to industrial relations tensions. This study aims to analyze the effectiveness of Public Relations (PR) management strategies and integrated media models in restoring brand equity post-crisis. The research method applied is descriptive qualitative with a conceptual analysis approach, relying on digital literature studies and the collection of secondary data from international reputation research firm reports and credible mass media documentation. The research results indicate that the drastic decline in the Brand Strength Index was successfully mitigated through a strategic narrative transition from service efficiency toward the reinforcement of the original "The Third Place" identity. The utilization of data-driven Owned Media channels through loyalty applications proved to be the most crucial instrument in maintaining consumer retention amidst the global boycott. The research conclusion emphasizes that brand resilience in the era of digital volatility depends not only on rhetoric but on the synchronization between adaptive leadership, operational transparency, and the integration of an agile PESO communication model. This study provides a theoretical contribution regarding the importance of managing "reputation capital" through consistent sustainability commitments to maintain a balance between profitability and corporate communication ethics in an increasingly polarized global market